Study on the Transmission Characteristic of Disk Type Magnetorheological Fluid with Variable Thickness - Huang Jin; Zhou Yi; Yuan Fapeng (Jixie chuandong)
Based on the rheological property of magnetorheological fluid（ MRF） and thermal drive characteristics of shape memory alloy（ SMA） spring,a new type of transmission device,which is based on the temperature field control of SMA to drive the MRF variable thickness to change the transmission torque is put forward. Its working principle is introduced,and the thickness calculation formula about relationship between thickness and SMA material,power,geometry parameters is derived. Based on the theory of magnetic circuit,the magnetic circuit model of the transmission device is established,the formula of magnetic potential is deduced. Based on the finite element simulation of two-dimensional magnetic field by using ANSYS software,and the distribution cloud of magnetic induction intensity under 4 different thicknesses is obtained,then the ability of torque transmission under different thickness is analyzed. The results show that the smaller the thickness of MRF,the greater torque can be transmitted,but MRF has the minimum thickness.